The script genre and its relationship with the creation of audiovisual materials (Research, Society and Development, 2022)
Script is a text that indicates and systematizes basic information that will constitute a previously guided work. It is known, therefore, that this is a multifaceted discursive genre with relevance in various areas of human interaction, whether in science, arts, health or education. Thus, the objective of this manuscript is to discuss the origin of the screenplay; to cover its definitions and concepts that are attributed to it; to evidence characteristics intrinsic to the genre, as well as its structural aspects. Moreover, this is a study of theoretical and conceptual nature carried out from documentary analysis, which focuses on the exploratory/bibliographical strand. It is evident, therefore, that the findings of this study corroborate the idea that the screenplay genre is understood as a kind of instructive guide that aims to aid the creative process of a given production, be it technical or artistic-literary. We conclude that, although surrounded by methodical and technical guidelines, this genre requires mastery of language, objectivity and simplicity for systemic achievement, in order to be enlightening, instructive and endowed with information that will serve as a basis in the construction of a kind of guiding map in a given human action.